OUTCOME OF RETROGRADE FLEXIBLE INTRAMEDULLARY NAILING IN FEMORAL DIAPPYSEAL FRACTURES OF CHILDREN - Shahab, Aamir; Hussain, Mumtaz; Imran, Muhammad; Shah, Sana Ali (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate the results of flexible intramedullary nailing in terms of postoperative leg length discrepancy and post operative pain during fracture resolution.Study Design: Case series.Place and Duration of Study: Department of Orthopedic Surgery, Jinnah Hospital Lahore, from Jan 2014 to Dec 2014.Methodology: One hundred and twenty patients (95 boys, 25 girls) having close fractures of femur diaphysis, between age of 5 to 9 years old were stabilized with titanium elastic nails system. Flynn et al scoring criteria was used to evaluate the outcome in terms of leg length discrepancy and visual analogue score for postoperative pain.Results: All patients were evaluated at 8 weeks for postoperative leg pain and leg length discrepancy (LLD). Excellent results (LLD